The prevalence of Listeria monocytogenes in Huacho sausages from some markets in Cercado de Lima - Pérez, María E. (2013)
Sixty Huacho sausage samples from Food Markets in Cercado de Lima, Peru, were analyzed in order to determine the prevalence of Listeria monocytogenes. These samples were collected in sterile containers and refrigerated, to be processed within 24 hours since collection in Microbiology laboratory from Pharmacy faculty of National University of San Marcos The USDA-FSIS methodology was used for microbiological analysis, which consists of three phases: Pre-enrichment of sample, Sample enrichment and Reseeding on selective agars and CAMP test. Listeria monocytogenes prevalence in Huacho sausages, was 78%. These results support that Huacho sausage is a food with a potential risk to the public health.